Reinventing a municipality by creating a festival of light. Case study, Loulé - Garcia-Ruiz, M. (2021)
Festivals of light are beginning to stand out, in the Portuguese scenario, as the new formula capable of responding to the needs of territorial reactivation, cultural and tourism promotion and internationalization. The artistic-cultural festivalization of the territory, outside the large nuclei, has specific characteristics to be reviewed in this study. In 2017 appears in Loulé the festival of light Luza. This cultural program is born with a multiple intention: on the one hand, to contribute to the internationalization of the council; introduce the municipality within cultural tourism circuits, with special interest in the low tourism season (winter); fight against the (pre) concept of the Algarve as a destination of sun and beach; strengthen the night economy; favor local artistic creation, and become a springboard for novice artists who intend to enter to the light art market. This project was supported by Algarve 365 and the Loulé City Council, corresponding to the main lines of intervention proposed by these entities: territory, identity, culture and tourism. In this case study, we will deepen the conditions that allowed for the development of this festival, reviewing the different public policies that participated in its implementation and the final design of the event. We will present the results of the ethnographic work developed with the different actors involved, as well as a study on the reception of Luza by visitors and residents of the city.